Art and architecture of the synagogue in late antique Palestine : in the shadow of the church - Milson, David. (Ancient Judaism and Early Christianity, 2007)
This study examines the material evidence for synagogues and churches in the Holy Land from the age of Constantine in the fourth century CE to the Arab conquest of the eastern provinces in the seventh century CE. Whereas scholars once viewed the growth of the Byzantine empire as time of persecution, a re-evaluation of the archaeological evidence indicates that Jews prospered along with their Christian neighbours. What influence did Christian art and architecture have on ancient synagogues? In the sixth century, one-third of all known synagogues in Palestine bear features similar to early Byzantine churches: basilical layouts, mosaic floors, apses, and chancel screens. Focusing on these features sheds light on how Jewish communities met the challenges posed by the Church's development into a major religious and political power. This book provides a critical analysis of the archaeological evidence as a basis for our better understanding of Jewish identity and community in late Antique Palestine.